Thomasville History Center - Merrill Papers, Documents 1978.32.0132-1978.32.0143 - Thomasville History Center (Valdosta State University Archives and Special Collections, 2024)
Merrill Papers, Documents 1978.32.0132-1978.32-0143. Community Archives: Thomasville History Center – Merrill Papers. Series 2, Box 1978-32. Folder 16. Items 132-143. Valdosta State University Archives and Special Collections.
1 electronic document (PDF), 44 scans, 45 pages. 6086084 bytes.
Keywords: Thomas County (Ga.); Thomasville (Ga.); Georgia--History--19th century; Georgia--History--20th century; Joseph Hansell Merrill (1862-1925); Charles Paine Hansell (1844-1919); Legal documents